A conceptual framework of different eccentric training methods - Handford, M. J.; Bright, T. E.; Mundy, P.; Lake, J.; Theis, N.; Hughes, J. D. (Strength and Conditioning Journal, 2023)
Various methods of eccentric training that aim to increase muscle mass or reduce ground contact time during a landing task have been extensively researched and practically examined. However, multiple methods to implement eccentric training currently exist; they differ in execution and intended training adaptions. There is a clear differentiation between an eccentric muscle action and an eccentric motion whereby a motion alludes to a downward movement of an exercise. The proposed eccentric motions are dissipating eccentrics, deceleration eccentrics, overcoming eccentrics, maximal eccentrics, and rebound eccentrics. These motions formulate into training methods and cues to allow practitioners to clearly differentiate the various eccentric training methods used in research and practice. This review proposes a new conceptual framework that clearly outlines the different forms of eccentric motions that fall into a desired eccentric training method.